Passive topological waveguide controlled by the boundary of the patterned area of external magnetic field with the hybrid quantum Hall and valley Hall effects - Yun-tuan Fang; Ping Gong; Sailing He (New Journal of Physics, 2023)
Topological waveguides with arbitrary pathway are desirable for many applications. In this paper we construct a triangular compound lattice consisting of magnetic dielectric rods. By breaking the space symmetry and the time-reversal symmetry, the structure generates topological edge states (TESs) from the hybrid quantum Hall effects and valley Hall effects. This topological edge waveguide pathway can be arbitrary arranged just by the external magnetic field. The hybrid topological phase provides a new and ultraflexible way to the reconfiguration of the TESs.